2021
DOI: 10.3390/ijms22147373
|View full text |Cite
|
Sign up to set email alerts
|

Features of Retinal Neurogenesis as a Key Factor of Age-Related Neurodegeneration: Myth or Reality?

Abstract: Age-related macular degeneration (AMD) is a complex multifactorial neurodegenerative disease that constitutes the most common cause of irreversible blindness in the elderly in the developed countries. Incomplete knowledge about its pathogenesis prevents the search for effective methods of prevention and treatment of AMD, primarily of its “dry” type which is by far the most common (90% of all AMD cases). In the recent years, AMD has become “younger”: late stages of the disease are now detected in relatively you… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 132 publications
(207 reference statements)
0
4
0
1
Order By: Relevance
“…Refer to panel A or table S1 for specific timing differences). Data sourced from the translating time database, as well as others: [16‒19, 26, 28, 30‒81]. A detailed list of the references that pertain to each feature, timepoint, and species can be found in online supplementary Table S1, as well as more detailed somite numbers, and developmental staging (Theiler staging for mouse, Witchi staging for rat, and McCrady staging for opossum).…”
Section: Resultsmentioning
confidence: 99%
“…Refer to panel A or table S1 for specific timing differences). Data sourced from the translating time database, as well as others: [16‒19, 26, 28, 30‒81]. A detailed list of the references that pertain to each feature, timepoint, and species can be found in online supplementary Table S1, as well as more detailed somite numbers, and developmental staging (Theiler staging for mouse, Witchi staging for rat, and McCrady staging for opossum).…”
Section: Resultsmentioning
confidence: 99%
“… 40 It occurs in the context of progressive alterations in cellular metabolism, stress responses, apoptosis, and protein aggregation and continues as cellular senescence ensues. 40 , 41 The features of retinal remodeling include photoreceptor degeneration, glial responses, neural reprogramming, and widespread rewiring, and there is an increase in the activity of these pathways before the eventual cell death seen in end-stage disease. 40 We found a relative decrease in pathways associated with retinal remodeling in the N-AMD group compared with the early or intermediate NN-AMD group in our study, including those involved in neuron projections and synapses.…”
Section: Discussionmentioning
confidence: 99%
“…They are later detected in the aorta–gonads–mesonephros (E10.5), fetal liver (E11.5) and then the bone marrow (E14–16.5), which becomes the dominant hematopoietic site in the adult state. Concurrently, retina development begins around E10 and matures postnatally [ 17 , 18 ]. Multiple studies have shown that some resident immune cells in the retina, typically microglia, are seeded in the eye from hematopoietic cells in the embryonic yolk sac, which migrate and proliferate in the retina [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%